A legal study of internet advertisement: medicine / Nurul Haizan Sukan and Marina Pilus - Sukan, Nurul Haizan; Pilus, Marina (Faculty of Law, 2014)
Medicine online advertisement has raised concern on consumer safety and wellness as the information contained in the advertisements can be misleading and false. Existing laws which govern medicine online advertising seem inadequate and inefficient to encounter the problems, and therefore it has limited the power of enforcement. Whereas medicine’s advertising via the internet is on the rise. Therefore, it is important to study whether the existing laws in Malaysia are comprehensive enough to protect consumers from false advertisements relating to medicines. Thus, the research objective is to reform the laws involved in medicinal advertisements. This study has examined the relevant laws and regulations in Malaysia so as to reveal gaps in existing knowledge, which has filled out of the research. The methodology used in this study is qualitative research. The primary resources such as Acts in Malaysia, UK, US and Singapore were analyzed. Secondary resources such as articles and journals were reviewed. Then empirical research was also carried out by conducting interviews with respondents from the Ministry of Health (MOH) and Federation of Malaysian Consumers Associations (FOMCA) as well as surveys from the consumers themselves. The analysis of laws, respondents’ interviews and consumer surveys have indicated that the current laws are not comprehensive to control the online advertising of medicine which resulted in the lack of enforcement power. The research findings confirm that there are lacunas in the existing law governing the medicine’s internet advertising. Therefore, we recommend a law reform.